Implementation of Accurate Accounting Information Systems To Mid-Scale Wholesale Company - Aloysius Putra; Adi Suryaputra (IC-ITECHS, 2014)
Company with medium scale has a problem in the recording business processes and financial reporting. With the increasing number of their transactions, it is not possible if it should always be handled manually. The purpose of this research is to determine the method of ACCURATE accounting information system implementation at mid-scale wholesale companies and to analyze the factors that influence the decision of a mid-scale wholesale company adopts accounting information systems for their business process. The method used in this research is by conduct a literature study and apply the method of implementation on the three mid-scale wholesale company. The authors formulate a right method of ACCURATE accounting information system implementation applied to mid-scale wholesale company, which through the process of needs analysis, setup database, and training. The authors also analyze and find the factors that influence a mid-scale wholesale company's decision to adopt an accounting information systems in the company, which is the background of the owner of the company, in addition to other factors such as price, time, and the scale and complexity of an accounting information system.